Photocatalytic activity enhancement with 4-trifluoromethylphenylacetylene-functionalized Cu2O cubes and rhombic dodecahedra from band structure modulation and use in boronic acid hydroxylation - Kuo-Chang, Chien; Wei-Yang, Yu; Jui-Cheng Kao; Yu-Chieh Lo; Chou, Jyh-Pin; Huang, Michael H (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
Surface 4-trifluoromethylphenylacetylene (4-TFMA) functionalization enables inert Cu2O cubes to exhibit a good photocatalytic activity. The modified rhombic dodecahedra also showed enhanced photocatalytic activity, but decorated octahedra actually delivered activity suppression. Scavenging experiments reveal that holes are more important than electrons for the photocatalytic activity of the functionalized cubes. Electron paramagnetic resonance (EPR) data agree with the observed photocatalysis results. Density functional theory (DFT) calculations disclose the emergence of one and two 4-TFMA-derived narrow bands within the band gap of the respective {110} and {100} surfaces of Cu2O to promote electron transfer through the molecule to the solution for radical generation, but no such band is present for the functionalized Cu2O {111} surface. Bader charge difference analysis also suggests promotion of charge transfer through 4-TFMA for the {100} and {110} surfaces of Cu2O, but the modification is less helpful over the {111} surface. The modified Cu2O cubes can also improve photocatalyzed arylboronic acid hydroxylation reactions. Conjugated molecular functionalization on semiconductor crystals is a powerful strategy for greatly enhancing electron transfer.